Harbuz D., Surma O., Mieshkov Ya. New atypical substrates for the phytopathogenic fungus Bipolaris sorokiniana (Sacc. in Sorokin) Shoemaker - Гарбуз, Д.І.; Сурма, О.С.; Мєшков, Я.В. (Львів : Інститут екології Карпат НАН України, 2021)
Using cultural and molecular genetic research we identified micromycete Bipolaris sorokiniana (Sacc. in Sorokin) Shoemaker on the atypical host plants: Acer negundo L., Ulmus sp. and Cytisus (Chamaecytisus) austriacus L. The nature of the relationship of the fungus with the host requires further investigation
Нові атипові субстрати для розвитку фітопатогенного гриба Bipolaris sorokiniana (Sacc. in Sorokin) Shoemaker
Keywords: гриби; фітопатогени; субстратна спеціалізація; деревні рослини